The Image of the Caliphs of the Umayyad Caliph in the book "History of the Caliphs" by Imam Jalaluddin al-Suyuti - Alsaeed, Khalid Abdullah (Journal of Humanities & Social Sciences, 2020)
The earliest historians, in their codification of the history of the Umayyad dynasty, relied on a number of some of the novelists of fads and whims, who were carrying hostility to the Umayyad state for doctrinal, intellectual or ethnic reasons. Unfortunately, these narratives formed a source that late historians still take advantage of in their writings. To find out the impact of these accounts on the late historians, this study came with the intent of clarifying the image of illiteracy among Imam Jalal al-Din Abd al-Rahman al-Suyuti in his book "The History of the Caliphs", and to verify whether al-Suyuti had merely relayed from his predecessors or had conjured up his deep knowledge of hadith science Subjecting these narratives to their criticism in terms of support and body.This study has concluded that Imam al-Suyuti's position on the succession of the Umayyad was no different in many or few from other historians; it depended on the transmission from the “History of Islam” to Imam al-Dhabi and other authors of literary works without subjecting their narratives to the approach of modern scholars based on criticism Novels and news. Moreover, we do not exclude that Al-Suyuti's bias towards the Abbasids, as evidenced by the book "The History of the Caliphs" and other works, as well as his close connection with the Abbasid caliph residing in Cairo, have a role in Al-Suyuti's deviation from the Umayyads and his prejudice against them.
Keywords: Al-Suyuti; the history of the caliphs; Banu Umayya; Banu al-Abbas